2001
DOI: 10.1093/protein/14.12.1001
|View full text |Cite
|
Sign up to set email alerts
|

Metal binding affinity and structural properties of an isolated EF-loop in a scaffold protein

Abstract: To establish an approach to obtain the site-specific calcium binding affinity of EF-hand proteins, we have successfully designed a series of model proteins, each containing the EF-hand calcium-binding loop 3 of calmodulin, but with increasing numbers of Gly residues linking the loop to domain 1 of CD2. Structural analyses, using different spectroscopic methods, have shown that the host protein is able to retain its native structure after insertion of the 12-residue calcium-binding loop and retains a native the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 61 publications
1
52
0
Order By: Relevance
“…The predicted 12-residue Ca 2ϩ -binding loop was directly inserted between Gly53 and Ala54 by PCR using an established protocol (70). The mutant with double mutations D5A and D12A (numbered according to the loop position of the inserted Ca 2ϩ -binding motif) was produced using standard PCR methods.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The predicted 12-residue Ca 2ϩ -binding loop was directly inserted between Gly53 and Ala54 by PCR using an established protocol (70). The mutant with double mutations D5A and D12A (numbered according to the loop position of the inserted Ca 2ϩ -binding motif) was produced using standard PCR methods.…”
Section: Methodsmentioning
confidence: 99%
“…The concentration of RUBCa was measured by its absorption at 280 nm with an extinction coefficient of 19,630 M Ϫ1 cm Ϫ1 , which was calculated according to previously described methods (22). The engineered proteins CD2.RUBCa and the mutant CD2.RUBCa.D5A/D12A were expressed and purified according to methods described previously (70). The molecular weights of CD2.RUBCa and the D5A/D12A mutant were also confirmed by matrix-assisted laser desorption ionization-time of flight mass spectrometry.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The geometrically predicted locations with 2-4 negatively charged ligands, strong negative surface potential, and functionally necessary residues were more likely to bind Ca 2ϩ . The model structures of CD2 variants with grafted potential Ca 2ϩ -binding sites of the CaSR were generated by SWISSMODEL (33,34 52 and Gly 53 of CD2 in the plasmid pGEX-2T (denoted as CD2-CaSR1 and CD2-CaSR2, respectively) by PCR using an established protocol (63). Two mutants, CD2-CaSR1-E228A/E229A and CD2-CaSR2-E378A/E379A, were also made by site-directed mutagenesis.…”
Section: Computational Prediction Of Camentioning
confidence: 99%
“…Different EF-hand-containing proteins bind Ca 2+ with different affinities, suggesting that a protein with multiple EF-hands, such as CaM, may bind Ca 2+ with a different affinity at each site (19)(20)(21)(22)(23)(24)(25)(26)(27)(28). It has therefore been suggested that CaM's four sites display different affinities and perhaps cooperativity (29,30).…”
mentioning
confidence: 99%